2014
DOI: 10.2967/jnumed.113.136481
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fc-Engineered Antibodies as Clearing Agents to Increase Contrast During PET

Abstract: Despite promise for the use of antibodies as molecular imaging agents in PET, their long in vivo half-lives result in poor contrast and radiation damage to normal tissue. This study describes an approach to overcome these limitations. Methods Mice bearing human epidermal growth factor receptor type 2 (HER2)–overexpressing tumors were injected with radiolabeled (124I, 125I) HER2-specific antibody (pertuzumab). Pertuzumab injection was followed 8 h later by the delivery of an engineered, antibody-based inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…This assumption is in accordance with findings that antibodies engineered to exhibit increased binding to FcRn at neutral pH are rapidly cleared from circulation. 24,25 This might also be the reason for the short half-life of the scDb-CH2 fusion protein, which showed increased binding to FcRn at neutral pH compared to acidic pH. No obvious differences in binding at acidic and neutral pH were observed for the other fusion proteins and IgG.…”
Section: Discussionmentioning
confidence: 98%
“…This assumption is in accordance with findings that antibodies engineered to exhibit increased binding to FcRn at neutral pH are rapidly cleared from circulation. 24,25 This might also be the reason for the short half-life of the scDb-CH2 fusion protein, which showed increased binding to FcRn at neutral pH compared to acidic pH. No obvious differences in binding at acidic and neutral pH were observed for the other fusion proteins and IgG.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the Abdegs tested in this study were indicated to work as potent agents in reducing IgG levels in antibody-mediated diseases and in inducing the rapid clearance of IgGtoxin or IgG-drug complexes (Vaccaro et al, 2005). Swiercz and colleagues have very recently developed a regimen of Abdeg delivery that was tested in an animal model of breast cancer, which resulted in improved tumor-to-blood ratios, reduced systemic exposure to radiolabel, and increased contrast during positron emission tomography (Swiercz et al, 2014). In spite of IVIG having efficacy in clearing radiolabeled antibodies during imaging, it requires higher doses due to the relatively poor competitive activity of the wild-type IgGs present in IVIG for FcRn binding (Jaggi et al, 2007;Swiercz et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Swiercz and colleagues have very recently developed a regimen of Abdeg delivery that was tested in an animal model of breast cancer, which resulted in improved tumor-to-blood ratios, reduced systemic exposure to radiolabel, and increased contrast during positron emission tomography (Swiercz et al, 2014). In spite of IVIG having efficacy in clearing radiolabeled antibodies during imaging, it requires higher doses due to the relatively poor competitive activity of the wild-type IgGs present in IVIG for FcRn binding (Jaggi et al, 2007;Swiercz et al, 2014). By contrast, Abdegs not only decreased systemic exposure to the radiolabel, but also could have significant practical advantages in clinical settings.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 1 more Smart Citation
“…To improve the specificity of cancer imaging, researchers have bound the most common contrast agents and nuclear medicine tracers to moieties that are thought to home to tumor biomarkers, including peptides, 36 antibodies, 37 and cells. 38 These are all targeting strategies that can be realized with MPI.…”
mentioning
confidence: 99%